Hybrid transvenous and surgical approach for the extraction of coronary sinus leads: A case series. Issue 7 (10th June 2022) - Ahmed, Ashraf; Arabia, Gianmarco; Bontempi, Luca; Cerini, Manuel; Salghetti, Francesca; Muneretto, Claudio; Mitacchione, Gianfranco; Milidoni, Antonino; Curnis, Antonio
Abstract: Background: Transvenous lead extraction is the standard therapy for cardiac device‐related infection. In some patients, however, a hybrid surgical and transvenous approach may be necessary. Methods and Results: We present three cases who underwent transvenous lead extraction for an infected CRT‐D system. In all cases the CS lead could not be retrieved transvenously due to extensive fibrosis. The lead was successfully extracted through left minithoracotomy in two patients and midline sternotomy in one patient. Conclusion: In cases where the coronary sinus lead shows severe fibrosis, a transvenous approach can be used to free the proximal part of the lead, while the distal adhesions can be removed surgically through a limited thoracic incision.